THE EFFECT OF PRICE, QUALITY OF SERVICE, BRAND IMAGE OF INTERNET PRODUCT VSAT IP BROADBAND QUOTA TO ALFAMART CUSTOMER SATISFACTION - Imam Subekhi; Baruna Hadibrata (Dinasti Publisher, 2020)
The aim of this research was to determine the effect of Price, Quality of Service and Brand Image on Customer Satisfaction of Alfamart Customer in using VSAT IP Broadband Quota service of PT Telkomsat. Number of respondents in this research is 248 respondents who work in Alfamart retail stores especially Jabodetabek area. The research method uses a questionnaire with SEM (Structural Equation Modelling) data analysis which is described in PLS (Partial Least Square) - SEM Application. The result of this research showed that the Price variable has a positive and significant effect on Customer Satisfaction. Quality of Service variable has a positive and significant effect on Customer Satisfaction. Then the Brand Image variable also has a positive and significant effect on Customer Satisfaction.